Impact of Bulgaria’s entry in the euro area for the banking and real sectors in the republic of Bulgaria and in particulary for the telecommunications industry - Avramov, Joseph (Yearbook Telecommunications, 2021)
The publication analyzes the advantages of the entry of the Republic of Bulgaria into the ERM 2 currency mechanism and the banking union. The first part indicates the benefits for our country for the banking sector of the Bulgarian economy, respectively for facilitating the payments of companies and citizens. The second part of the publication refers to the advantages for the real sector of the Bulgarian economy, respectively for the Telecommunications sector. In conclusion, some not very significant shortcomings are indicated, which will occur after Bulgaria’s accession to the euro area.